Planned improvement actions based on patient safety incident reports in Estonian hospitals: a document analysis - Margus Lember; Karolin Toompere; Mari Kangasniemi; Kaja Pölluste; Ere Uibu (BMJ Open Quality)
Aim Aim of this study was to describe and analyse associations of incidents and their improvement actions in hospital setting.Methods It was a retrospective document analysis of incident reporting systems’ reports registered during 2018–2019 in two Estonian regional hospitals. Data were extracted, organised, quantified and analysed by statistical methods.Results In total, 1973 incident reports were analysed. The most commonly reported incidents were related to patient violent or self-harming behaviour (n=587), followed by patient accidents (n=379), and 40% of all incidents were non-harm incidents (n=782). Improvement actions were documented in 83% (n=1643) of all the reports and they were focused on (1) direct patient care, (2) staff-related actions; (3) equipment and general protocols and (4) environment and organisational issues. Improvement actions were mostly associated with medication and transfusion treatment and targeted to staff. The second often associated improvement actions were related to patient accidents and were mostly focused on that particular patient’s further care. Improvement actions were mostly planned for incidents with moderate and mild harm, and for incidents involving children and adolescents.Conclusion Patient safety incidents-related improvement actions need to be considered as a strategy for long-term development in patient safety in organisations. It is vital for patient safety that the planned changes related to the reporting will be documented and implemented more visibly. As a result, it will boost the confidence in managers’ work and strengthens all staff’s commitment to patient safety initiatives in an organisation.